Pain tolerance and cardiorespiratory fitness in women with dysmenorrhea - Fábio Marcon Alfieri; Karoline Mayara de Aquiles Bernardo; Yasmim da Silva Pinto; Natália Cristina de Oliveira Vargas e Silva; Leslie Andrews Portes (Revista Dor, 2017)
ABSTRACT BACKGROUND AND OBJECTIVES: Hormonal changes are known to affect quality of life of women and may interfere in pain tolerance and cardiorespiratory exercise performance. Thus, the aim of this study was to evaluate and compare pressure pain tolerance threshold and cardiorespiratory fitness in women in luteal and follicular phases of the menstrual cycle. METHODS: University students aged 18-30 years old with a regular menstrual cycle were evaluated for cardiorespiratory fitness (ergospirometry), pain perception through the visual analog scale and pressure pain tolerance (algometry). RESULTS: When evaluated in follicular phase, the 13 participants exhibited a significant increase (p<0.001) in pain perception. Follicular phase also resulted in a significant reduction in pressure pain tolerance in all sites evaluated (p<0.05). At rest, follicular phase resulted in a significant increase (p<0.05) in systolic and diastolic blood pressure, but no effect was observed in heart rate. At peak exercise, follicular phase caused a significant reduction (p<0.05) in heart rate and peak VO2, without significantly affecting speed, test duration and indicators of metabolism efficiency. CONCLUSION: Healthy women with dysmenorrhea show higher pain perception in follicular phase, which results in increased pain sensitivity and prejudice in hemodynamic aspects at rest and during exercise, as well as in cardiorespiratory fitness, without significant alterations in metabolism.